"Aerogel-like" polysiloxane-polyurethane hybrid foams with enhanced mechanical and thermal-insulating properties. (8th September 2021) - Verdolotti, Letizia; Oliviero, Maria; Lavorgna, Marino; Santillo, Chiara; Tallia, Francesca; Iannace, Salvatore; Chen, Shu; Jones, Julian R.
Abstract: New organic-inorganic polyurethane-based hybrids with enhanced mechanical properties and thermal insulation properties are reported. Polyurethane-based hybrids are characterized by the intimate interactions of their inorganic and organic co-networks and prepared by sol-gel approach, have exhibited properties exceeding those of polyurethane foams, e.g. enhanced thermal stability, durability and thermal insulating effectiveness. However, mechanical properties have previously been poor. Here, new porous organic-inorganic materials consisting of a polyurethane network modified by in-situ formation of aerogel-like polysiloxane domains, were developed. They exhibit a multiscale-porosity which enhances the insulation, mechanical and thermal properties. The synthesis was performed through a novel stepwise process consisting of: preparation of a siloxane precursor based on methyl-triethoxysilane and tetraethoxysilane; functionalization of traditional polyol for polyurethane foams with 3-(triethoxysilanepropyl)isocyanate as coupling agent; use of suitable catalysts and silicone surfactants; and foaming with methylene-di-isocyanate compound. The siloxane precursors and coupling agent led to formation of "aerogel-like" polysiloxane domains within the walls and struts of the polyurethane foams. The synthesis method enabled increased incorporation of the "aerogel-like" polysiloxane structures into the foams, compared to literature, with 20 wt% SiO2, reducing thermal conductivity of the hybrid foams 30% compared with pristine polyurethane, in addition to significant improvement in thermal stability and mechanical properties. Graphical abstract: Image 1